TRANSPARANSI PEREKRUTAN APARAT DI DESA PILOLALENGA KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Sri Lestari Gintulangi (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2018)
This study aims to determine the recruitment of village officials in Pilolalenga Village, Dungaliyo District, Gorontalo Regency. The method used in this research is descriptive qualitative. The results showed that of the five indicators measured namely  guaranteed  access  as  clear  and  accurate  information,  freedom  for everyone to obtain information, governance, information about policy making, implementation and the results achieved have not shown the existence of a transparent village apparatus recruitment system related to the time details, terms and conditions of the recruitment process for village officials. This can be seen from the limited community access to obtain clear information related to the implementation of village apparatus recruitment so that the implementation of village  apparatus  recruitment  is  only  followed  by  a  small  portion  of  the community. Keywords: Transparency, Recruitment of Village Officials